On Trade Relations between Russia and the Emirate of Bukhara (Late XVIII th To Mid XIX th Centuries) - Shokhida Khaidarovna Davurova (Researchparks Publishing, 2022)
The article covers trade relations of the Russian Empire with Bukhara Emirate at the end of XVIII - beginning of XIX centuries. It analyzes the processes of deepening and expanding bilateral trade, import and export items between the countries.